Proceeding of the 44th ACM Technical Symposium on Computer Science Education 2013
DOI: 10.1145/2445196.2445377
|View full text |Cite
|
Sign up to set email alerts
|

Using app inventor in a K-12 summer camp

Abstract: Educators are often seeking new ways to motivate or inspire students to learn. Our past efforts in K-12 outreach included robotics and media computation as the contexts for teaching Computer Science (CS). With the deep interest in mobile technologies among teenagers, our recent outreach has focused on using smartphones as a new context. This paper is an experience report describing our approach and observations from teaching a summer camp for high school students using App Inventor (AI). The paper describes tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 8 publications
3
33
0
3
Order By: Relevance
“…It is a tangible technology, very common and famous among young people. Educators could take advantage of devices like tablets and smart phones for motivating in computer science topics [22]. Finally, some researchers additionally use unplugged computer science activities [7] or even textual programming languages [12].…”
Section: Motivationmentioning
confidence: 99%
“…It is a tangible technology, very common and famous among young people. Educators could take advantage of devices like tablets and smart phones for motivating in computer science topics [22]. Finally, some researchers additionally use unplugged computer science activities [7] or even textual programming languages [12].…”
Section: Motivationmentioning
confidence: 99%
“…Morelli and Colleagues asserted that AI is easy to learn, accessible and lead students to problem solving instead of coding [47]. It is also indicated that AI is a highly motivating and powerful instructional tool [49]. Instructors have been using AV software for different educational aims in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used App Inventor in summer camps and other outreach activities for K12 students for several years now [1], [2], [3], [4], [5]. App Inventor has also been effectively used for professional development workshops for K12 teachers [6], [7], as well as introductory computing courses at the college level [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%